IIIT workshop on Islamization of Knowledge - July 9-11, 2019 - Knowledge and Civilization in Islam (Text Book) - Shehu, Fatmir Mehdi (2019)
Main Objectives: - This Text Book aims at: dealing with two important concepts – Knowledge and Civilization, from Islamic Perspective, describing the contribution of Muslim scholars and scientists in different fields of knowledge and science throughout the history of Islamic Civilization, and discussing some contemporary challenges faced by the Muslim Ummah and their responses.